FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA DALAM PEMILIHAN KARIR SEBAGAI AKUNTAN PUBLIK (Studi Kasus Pada Mahasiswa Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Islam Malang dan Universitas Merdeka Malang) - Akhmad Faisal; Moh. Amin; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study was conducted to determine the effect of financial rewards, labor market considerations, family environment, personality, professional recognition and work environment on student interest in choosing a career as a public accountant. This research was conducted on students majoring in accounting at the Islamic University of Malang and Independent University of Malang. The data collection method used in this study was to distribute questionnaires to respondents in the form of written questions. The sample used in this study were active undergraduate students (S1) in the 2018 Faculty of Economics and Business Accounting study program. The method of determining the sample used was the purposive sampling method. The data analysis method used in this study used multiple linear regression analysis. Based on the results of SPSS 16.0 analysis, this study shows that Personality and Professional Recognition have a positive effect on student interest in choosing a career as a public accountant. While the variables of Financial Rewards, Labor Market Considerations, Family Environment, and Work Environment have no effect on students' interest in choosing a career as a public accountant. Keywords: Student interest in choosing a career as a public accountant, Financial Awards, Job Market Considerations, Family Environment, Personality, Professional Recognition, and Work Environment.